2015
DOI: 10.1016/j.socscimed.2015.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of public deliberation methods for gathering input on issues in healthcare: Results from a randomized trial

Abstract: Chicago, IL; Sacramento, CA; Silver Spring, MD; and Durham, NC, capturing a sociodemographically diverse sample with specific attention to ensuring inclusion of Hispanic, African-American, and elderly participants. Of 1774 people recruited, 75% participated: 961 took part in a deliberative method and 377 participants comprised the RMO control group. To assess effectiveness of the deliberative methods overall and of individual methods, we evaluated whether mean pre-post changes on a knowledge and attitude surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
96
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(99 citation statements)
references
References 29 publications
1
96
0
2
Order By: Relevance
“…In this synthesis, we found that the mechanism of political commitment works when the health problem identified affects the common good, when it is considered a priority of the users (Crawford et al 2003;Carman et al 2015) and when the identified health problem is clear and specific (Abelson et al 2003;Crawford et al 2003). Intangible outcomes of public participation brought about by broadly defined issues promote the notion that nothing comes out of it.…”
Section: Context Of Political Commitmentmentioning
confidence: 95%
See 2 more Smart Citations
“…In this synthesis, we found that the mechanism of political commitment works when the health problem identified affects the common good, when it is considered a priority of the users (Crawford et al 2003;Carman et al 2015) and when the identified health problem is clear and specific (Abelson et al 2003;Crawford et al 2003). Intangible outcomes of public participation brought about by broadly defined issues promote the notion that nothing comes out of it.…”
Section: Context Of Political Commitmentmentioning
confidence: 95%
“…Others also identified the possible outcome of public participation (Alborz et al 2002;Restall and Kaufert 2011;Carman et al 2015;Conklin et al 2015). Although there has been an increasing number of studies of public participation in health policy and planning, no studies have focused on the factors that provide explanations on how and why effectiveness could be achieved in this field.…”
Section: Public Participation In Health Policy and Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…9 While it is recognized as a knowledge translation strategy, 10 it also has the potential to be an approach to data collection in qualitative research. 9 Several studies have documented that deliberative dialogue can significantly contribute to change practice and policy, [11][12][13] overcoming challenges such as irrelevant evidence and access to scientific knowledge, and making research evidence easier to use in decision-making. 10 Policies formed through deliberative dialogue comprise technical and real-world knowledge; therefore they are more legitimate, feasible, better framed, more accountable, and inclusive.…”
mentioning
confidence: 99%
“…10 Policies formed through deliberative dialogue comprise technical and real-world knowledge; therefore they are more legitimate, feasible, better framed, more accountable, and inclusive. [11][12][13][14] Deliberative processes are well suited to the health field because they can meet the broader objectives of stimulating debate, improving the understanding of complex issues, and encouraging consensus about health services priorities. 15 However, there has been very limited experience in nursing with deliberative dialogue.…”
mentioning
confidence: 99%